Damage by Diatraea spp. (Lepidoptera: Crambidae) in the Córdoba-Golfo sugarcane region, Veracruz - Cruz-Tobón, Marisol; Hernández-Rosas, Francisco; Silva-Rojas, Hilda Victoria; Serna-Lagunes, Ricardo; Rodríguez-Lagunes, Daniel Arturo; Llarena-Hernández, Régulo Carlos (Revista Mexicana de Ciencias Agrícolas, 2023)
The stem borer (Diatraea spp.) is the primary pest of sugarcane worldwide. In the Córdoba-Golfo sugarcane region, Veracruz, Mexico, the distribution and damage by the Diatraea spp. complex has been little studied, which causes biases in the estimation of the impact. The objective of the study was to determine the spatial-temporal damage by Diatraea spp. larvae during the production cycle from January 2020 to January 2021. A total of n=21 plots were selected in seven localities, and the number of stems bored by Diatraea spp. larvae was determined, with which isodensity maps were generated with the Suprakml software and Google Earth Pro®. The interaction between crop age, studied sites, and bored stems was analyzed with a two-way variance test (α< 0.05) with the Rstudio v3.6 software. The distribution of damage by Diatraea spp. larvae showed a clustered spatial arrangement, with the largest number of stems bored in the Actopan site, while in Palmillas, the population behaved as a focus of infestation. The number of bored stems was constant, but from January to April 2020, the damage increased, coinciding with the vegetative development period of the crop. The interaction analysis presented a negative effect since, as the age of the crop increased, the damage decreased, while Palmillas showed statistical differences with respect to the rest of the sites, so it is concluded that this site is the possible nucleus of dispersion of the pest.